O fio de água : o Porto e as obras portuárias (Douro-Leixões) - Alves, Jorge Fernandes (2013)
Funded on the historic relationship between the town of Oporto and the use of water- ways as a means of transportation, this work is a historical analysis of the major public works carried out in the seaports of Douro and Leixões, in which the authors also describe the technical and economic potential of the major successive projects.